Reduced LYNX1 expression in transcriptome of human iPSC-derived neural progenitors modeling fragile X syndrome - Talvio, Karo; Minkeviciene, Rimante; Townsley, Kayla G.; Achuta, Venkat Swaroop; Huckins, Laura M.; Corcoran, Padraic; Brennand, Kristen J.; Castrén, Maija L. (Frontiers in Cell and Developmental Biology, 2022)
Lack of FMR1 protein results in fragile X syndrome (FXS), which is the most common inherited intellectual disability syndrome and serves as an excellent model disease to study molecular mechanisms resulting in neuropsychiatric comorbidities. We compared the transcriptomes of human neural progenitors (NPCs) generated from patient-derived induced pluripotent stem cells (iPSCs) of three FXS and three control male donors. Altered expression of RAD51C, PPIL3, GUCY1A2, MYD88, TRAPPC4, LYNX1, and GTF2A1L in FXS NPCs suggested changes related to triplet repeat instability, RNA splicing, testes development, and pathways previously shown to be affected in FXS. LYNX1 is a cholinergic brake of tissue plasminogen activator (tPA)-dependent plasticity, and its reduced expression was consistent with augmented tPA-dependent radial glial process growth in NPCs derived from FXS iPSC lines. There was evidence of human iPSC line donor-dependent variation reflecting potentially phenotypic variation. NPCs derived from an FXS male with concomitant epilepsy expressed differently several epilepsy-related genes, including genes shown to cause the auditory epilepsy phenotype in the murine model of FXS. Functional enrichment analysis highlighted regulation of insulin-like growth factor pathway in NPCs modeling FXS with epilepsy. Our results demonstrated potential of human iPSCs in disease modeling for discovery and development of therapeutic interventions by showing early gene expression changes in FXS iPSC-derived NPCs consistent with the known pathophysiological changes in FXS and by revealing disturbed FXS progenitor growth linked to reduced expression of LYNX1, suggesting dysregulated cholinergic system.